Three new proctophyllodine feather mites (Acari: Proctophyllodidae) from passerines in Brazil (Aves: Passeriformes) - Hernandes, Fabio Akashi (Taylor & Francis, 2013)
Three new species of the feather mite subfamily Proctophyllodinae are described from passerines in Brazil: Nycteridocaulus guaratubensis sp. nov. from Phylloscartes kronei (Rhynchocyclidae), Mimicalges neopelmae sp. nov. from Neopelma pallescens (Pipridae) and Atrichophyllodes leucopterus sp. nov. from Pyriglena leucoptera (Thamnophilidae). The females of Mimicalges are described for the first time. http://www.zoobank.org/urn:lsid:zoobank.org:pub:88E17B8B-CBFD-4B05-94B9-23FFCC34910. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: Analgoidea; Astigmata; feather mites; Neotropical region; taxonomy